2008
DOI: 10.1136/bmj.a2338
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic spread of happiness in a large social network: longitudinal analysis over 20 years in the Framingham Heart Study

Abstract: Objectives To evaluate whether happiness can spread from person to person and whether niches of happiness form within social networks. Design Longitudinal social network analysis. Setting Framingham Heart Study social network. Participants 4739 individuals followed from 1983 to 2003. Main outcome measures Happiness measured with validated four item scale; broad array of attributes of social networks and diverse social ties. Results Clusters of happy and unhappy people are visible in the network, and the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
979
14
28

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,531 publications
(1,071 citation statements)
references
References 64 publications
50
979
14
28
Order By: Relevance
“…Importantly, these social networks can affect collective community behaviour which might have an impact on community resilience to disasters. Studies have suggested social networks impact on, among other things, local governance (Beall 2001;Schafft and Brown 2000), health levels (Berkman 2000), child survival (Adams et al 2002) and even happiness (Fowler and Christakis 2008).…”
Section: Disaster Communitiesmentioning
confidence: 99%
“…Importantly, these social networks can affect collective community behaviour which might have an impact on community resilience to disasters. Studies have suggested social networks impact on, among other things, local governance (Beall 2001;Schafft and Brown 2000), health levels (Berkman 2000), child survival (Adams et al 2002) and even happiness (Fowler and Christakis 2008).…”
Section: Disaster Communitiesmentioning
confidence: 99%
“…The most surprising aspect of this research, at least for our purpose, was that the most reliable indicator of spread of happiness was physical proximity. On the basis of their own research, and that of others, the authors even go so far as to state that ''close physical proximity or coresidence is indeed necessary for emotional states to spread'' (Fowler and Christakis 2008). This conclusion also has support from evolutionary psychology, according to which contagious expressions of happiness tend to enhance social bonds-which in turn is an evolutionary advantage.…”
Section: The Relative Value Of Actual and Virtual Friendshipsmentioning
confidence: 86%
“…In a comprehensive, 20-year longitudinal study of happiness in a large social network, Fowler and Christakis (2008) came to the conclusion that people who are surrounded by many happy people, in particular those who are central in the network, had a significantly higher degree of well-being. The most surprising aspect of this research, at least for our purpose, was that the most reliable indicator of spread of happiness was physical proximity.…”
Section: The Relative Value Of Actual and Virtual Friendshipsmentioning
confidence: 99%
“…The case for exploring 'weaker' ties in the context of SMS is supported by the recognition that a salient feature of contemporary society is a less centralised and broader diffusion of support networks and distributed knowledge that has grown alongside or outside of a 'primary' set of intimate relationships [6,[15][16][17][18]). A growing interest in the role and function of weak ties has been linked to a recognition of the fragmentation of social life, generating a complex set of impersonal, transient second level networks and associations made up of neighbours, work colleagues, and taxi-drivers.…”
Section: Mapping Weak Tie Involvement In Chronic Illness Relationshipsmentioning
confidence: 99%